Managing of solid waste on construction site - Raja Muhamad Anuar, Raja Mustafa (2008)
Construction solid waste is a waste in solid form which is defined as useless or unwanted. It generated from building construction, demolition and refurbishment works. It has become as one of major environmental problems faced by the most municipalities.This paper based on study that has been conducted which involves types of solid wastes and factors that contribute to the waste on construction site. This study also focused on method used in managing solid waste on site. Two (2) methods have been used to achieve the objectives of this study which are questionnaire and interview. 34 respondents who are from construction company and local authorities in Pahang gave their feedback by answering the questionnaires. Data from questionnaire have been analyzed using average index (A!). Interview through site visit is carried out in Pekan, Pahang. It is done to get further information about methods used in managing waste on site. In conclusion, types of solid waste, factors contribute to waste on site and methods of managing solid waste have been identified. This study found that there are 8 types of construction waste on site such as concrete, asphalt, wood or timber, glass, plastic, metal or steel, roofing and brick or block. There are several factors contribute to waste on site such as lack of recycling facilities within the study region, mishandling, weather, inadequate storage, lack of communication between leader and worker, design changes,vandalism, ordering error, role of project manager and low quality material. The study result also shows the popular method choose by respondent to handle the solid waste which is dispose it and this is followed by reducing, recycling and reuse method.